2012
DOI: 10.1371/journal.pone.0038891
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of WHO Guidelines in Maternal Health Using the AGREE II Assessment Tool

Abstract: In 2007, the World Health Organization (WHO) received a criticism for a lack of transparency and systematic methods in the development of guidelines, which were at that time perceived as substantially driven by expert opinion. In this paper we assessed the quality of maternal and perinatal health guidelines developed since then. We used the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool to evaluate the quality of methodological rigour and transparency of four different WHO guidelines publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 13 publications
8
47
2
Order By: Relevance
“…This finding is not dissimilar to those of many other systematic reviews of guidelines targeting other health conditions (eg, endocrine disorders, 40 acute gastroenteritis, 42 and cardiovascular disease 49 ). Unlike another review, 50 in which authors showed an increase in domain scores in more recent guidelines, we did not find the same trend in our review. Possible reasons could be a lack of awareness of the AGREE II criteria or inadequate or lack of reporting them.…”
Section: Strengths and Limitations Of Pediatric Pain Clinical Guidelinescontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is not dissimilar to those of many other systematic reviews of guidelines targeting other health conditions (eg, endocrine disorders, 40 acute gastroenteritis, 42 and cardiovascular disease 49 ). Unlike another review, 50 in which authors showed an increase in domain scores in more recent guidelines, we did not find the same trend in our review. Possible reasons could be a lack of awareness of the AGREE II criteria or inadequate or lack of reporting them.…”
Section: Strengths and Limitations Of Pediatric Pain Clinical Guidelinescontrasting
confidence: 99%
“…Similar to Polus and colleagues 50 in their appraisal of World Health Organization guidelines using the AGREE II Instrument, reviewers found that providing an overall assessment score was challenging. This difficulty could be related to the lack of scoring detail provided in the AGREE II training resource, which did not specify how scores corresponded with decisions for recommending the guideline for use in practice.…”
Section: Strengths and Limitations Of The Agree II Instrumentmentioning
confidence: 71%
See 2 more Smart Citations
“…3,4 With such concerns, the AGREE Collaboration (Appraisal of Guidelines, Research and Evaluation) created a 23-item tool (AGREE II tool) targeting 6 quality-related domains to assess the quality of CPGs; this AGREE II tool has become an internationally well-accepted standard to evaluate guidelines. 5,6 Faced with conflicting and inconsistent guidelines, urologists rightly maintain a healthy skepticism and are able to identify reliable guidelines. To determine the qualities, similarities and differences in standards of care across the available guidelines, we critically reviewed all available recent CPGs using the AGREE II tool for the diagnosis, assessment and treatment of non-neurogenic male LUTS.…”
Section: Introductionmentioning
confidence: 99%